Long-term trends in Neisseria gonorrhoeae and Chlamydia trachomatis prevalence among brothel-based female sex workers in Denpasar, Bali, Indonesia - Dewa Nyoman Wirawan; Emily Rowe; Fonny Silfanus; Putri Pidari; Gusti Ayu Satriani; Dewa Suyetna (Public Health and Preventive Medicine Archive, 2013)
The objective of this study is to analyze the long-term trends of Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) infections and risk factors among female sex workers (FSW) in Denpasar, Bali, Indonesia. In order to understand the long-term trends, secondary data was examined from the years 1997-1999, 2004, 2007, 2009 and 2010; to analyze associated factors, data from 2010 was used. Analysis indicates an overall decrease of NG prevalence in Bali from 60.5% (95%CI: 56.6-64.5) in 1997 to 22% (95%CI: 16.8-27.1) in 2010. CT prevalence has also experienced a long term decline but not to the same degree as NG. Findings from analysis of surveys in 2004 and 2010 indicate that there is a strong relationship between condom use in the last sexual transaction with NG infection (p=0.02), duration of sex work (p=0.02), number of clients in the last week (p=0.01), clinic visit intervals and clinic visit frequency. CT prevalence was associated with the number of clients (p=0.04) and clinic visit frequency. Unfortunately, these were the only variables collected therefore a multivariate analysis was not possible. High prevalence of both NG and CT is associated with the high mobility of FSW and low condom use. There is a significant long-term decrease of NG prevalence from 60.5% to 22%. However, CT experienced an insignificant long term decrease from 41.3% to 35%.